Aortopulmonary collaterals in neonates with d-transposition of the great arteries – Clinical significance early after arterial switch operation. (1st May 2018) - Wipf, Alexandra; Christmann, Martin; Navarini-Meury, Susanne; Dave, Hitendu; Quandt, Daniel; Knirsch, Walter; Kretschmar, Oliver
Abstract: Objectives: Purpose of this study is to evaluate the clinical significance of major aortopulmonary collateral arteries (MAPCAs) during the early postoperative course after arterial switch operation (ASO) in d-transposition of the great arteries (dTGA). Methods: Clinical data of 98 patients with simple dTGA between January 2007 and December 2016 at the University Children's Hospital Zurich, Switzerland were analyzed retrospectively. Results: 37 from 98 patients (38%) required cardiac catheterization (CC) due to an early complicated postoperative course or difficult coronary transfer due to special coronary anatomy. In 15 (15%) patients, hemodynamically relevant MAPCAs were found during CC and coil embolization was performed. Patients with relevant MAPCAs had a significantly longer PICU stay (7 versus 6 days, p = 0.021), longer hospital stay (41 versus 27 days, p = 0.005), longer mechanical ventilation time (5 versus 3 days, p = 0.005), longer need for inotropic support (5 versus 4 days, p = 0.001) and delayed chest closure time (3 versus 2 days, p = 0.030) in those in whom it was left open in comparison to all other patients. In patients having CC, pre-surgery oxygen saturation was significantly lower in patients with relevant MAPCAs (58% vs 70%, p 0.019). Echocardiography had a sensitivity of 53% and a specificity of 100% in detecting relevant MAPCAs, accurately. Conclusions: MAPCAs are frequently found in dTGA patients and can be associated with lower baseline oxygen saturation and a prolonged postoperative course after ASO. Transthoracic echocardiography cannot replace CC as diagnostic tool. If significant MAPCAs are suspected, early CC should be performed for diagnostic and therapeutic reasons. Highlights: MAPCAs are not a rare finding in dTGA. MAPCAs can be responsible for a complicated postoperative course after ASO. Lower pre-surgery oxygen saturation is associated to relevant MAPCAs.